MEKANISME PENYALURAN PEMBIAYAAN MURABAHAH PADA MASYARAKAT PEDESAAN DI UNIT PENGELOLA KEGIATAN SYARIAH MANDIRI KECAMATAN SELAKAU - Nuri Arini (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
The Activity Management Unit is an institution engaged in channeling financing to people who need capital to run their business. The Activity management unit applies sharia principles with a buying and selling system using a Murabahah contract. Murabahah contract is a sale and purchase contract of an item plus an agreed margin. Here the Activity Management Unit buys goods needed by customers from Suppliers and then sells them back to customers with additional profits according to the agreement. This study uses a descriptive qualitative research type, which only describes situations and events originating from interviews, observations, and documentation on the Mechanism of Distribution of Murabahah Financing in Rural Communities in the Syariah Mandiri Activity Management Unit (UPK) Selakau District. The results of this study show that the Mechanism for Distribution of Murabahah Financing to Rural Communities in the Mandiri Syariah Activity Management Unit (UPK) in Selakau District is in accordance with its application, especially the contract used, namely the Murabahah contract which is in accordance with DSN Fatwa No.04/DSN-MUI/IV/2000 which states that the bank buys goods needed by the customer on behalf of the bank itself and this purchase must be lawful and free of usury